Conversational pragmatics: memory reporting strategies in different social contexts - Martín-Luengo, Beatriz; Luna, Karlos; Shtyrov, Yury (Frontiers in Psychology, 2023)
Previous studies in conversational pragmatics have showed that the information people share with others heavily depends on the confidence they have in the correctness of a candidate answer. At the same time, different social contexts prompt different incentive structures, which set a higher or lower confidence criterion to determine which potential answer to report. In this study, we investigated how the different incentive structures of several types of social contexts and how different levels of knowledge affect the amount of information we are willing to share. Participants answered easy, intermediate, and difficult general-knowledge questions and decided whether they would report or withhold their selected answer in different social contexts: formal vs. informal, that could be either constrained (a context that promotes providing only responses we are certain about) or loose (with an incentive structure that maximizes providing any type of answer). Overall, our results confirmed that social contexts are associated with different incentive structures which affects memory reporting strategies. We also found that the difficulty of the questions is an important factor in conversational pragmatics. Our results highlight the relevance of studying different incentive structures of social contexts to understand the underlying processes of conversational pragmatics, and stress the importance of considering metamemory theories of memory reporting.